STUDI TENTANG EVALUASI PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI TINGKAT DESA DI KABUPATEN SIGI TAHUN 2014-2015 - Putri, Rizki Ayuning Eko (Katalogis, 2015)
The purpose of this study are: to know and analyze the percentages proposed program development plan proposed since musrenbangdes until musrenbang SKPD in Sigi, the cost spent on planning forums at village and sub-district to produce the proposed development program in Sigi, and allocation of funds with no accommodation of the proposed development program at the village level in Sigi years 2014-2015. The results of this study are: the percentage of the proposed program development plan proposed by each of the selected villages in each district an average of 6% -14% only the plans that can be implemented, the allocation of funds for planning forums at village and sub-district levels vary, not at par between one village to village, and when referring to the allocation of funds musrenbangdes their respective villages in three districts, that the proposed development program is set to the value of funds on average between one village to another village.